P-106 DIAGNOSTIC ACCURACY OF SHEAR-WAVE ELASTOGRAPHY IN METABOLIC DYSFUNCTION–ASSOCIATED STEATOTIC LIVER DISEASE, A SINGLE CENTER REPORT - LUIS CARLOS ARAYA ACERO; Esteban Ruiz Blard (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Metabolic dysfunction-associated steatotic liver disease (MASLD), the most prevalent liver disease in history, requires non-invasive tests to assess fibrosis and determine follow-up. The limited access and high cost of FibroScan necessitate the validation of other alternatives. The objective of this study is to assess the diagnostic accuracy of short-wave elastography (SWE). Patients / Materials and Methods: This single-center, retrospective study was conducted from 2022 to 2024. We identified patients who underwent SWE as a non-invasive test to assess liver fibrosis. Clinical and demographic characteristics were ascertained by reviewing medical records. Clinical evidence of advanced fibrosis was defined by the presence of clinically significant portal hypertension (CSPH).SWE (Philips Affiniti 70G Ultrasound with ElastQ imaging software, Koninklijke Philips N.V., Amsterdam, Netherlands) was performed after a 6-hour fast, with patients in a slight left lateral decubitus position. At least 10 measurements were taken for each patient. Mean and median rigidity were measured in kilopascals (KPa), with >13 KPa defined as the cut-off to rule in compensated advanced chronic liver disease (cACLD) and <9 Kpa to rule out significant fibrosis.Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated for the cut-off score. Results and Discussion: A total of 86 patients were identified, with a mean age of 55 (range 22-79), 68.8% females, and 47.8% with MASLD as the predominant etiology of chronic liver disease. Overall, 31.4% were previously known to have CSPH. Within the MASLD subgroup, the FIB-4 score had a 100% PPV (under 1.31) compared to 80% with SWE to rule out fibrosis but with a higher sensitivity compared to FIB-4 (53.3% vs 35.7%). Regarding ruling in advanced fibrosis, SWE had a sensitivity of 92.9% vs 88.9% in FIB-4 with a NPV of 80%. See Table 1. Conclusions: SWE has an excellent NPV to rule out advanced fibrosis and higher sensitivity than FIB-4 to rule out fibrosis. Recent guidelines recommend using at least two non-invasive tests to assess fibrosis. While the study is limited by its power and retrospective nature, the results show that SWE can be used as a first or second test when assessing fibrosis. Further studies with larger populations are needed to establish it as a viable option.